Severe Hirsutism in Non Classic Congenital Adrenal Hyperplasia: A Case Report and Literature Review - Emini, Merita; Olldashi, Blertina; Qovanaj, Blerina (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Non-classic congenital adrenal hyperplasia (NCAH) is a relatively common disorder, but very often, it remains undiagnosed. Clinical appearance of NCAH can be asymptomatic at birth. Symptoms are presented more often in late childhood, adolescence, or later in life caused by excessive androgen secretion. CASE REPORT: We report the case of 27-year-old girl with 2 years history of high-grade of hirsutism, hair loss on the front of scalp with female pattern hair loss, (grade II according to Ludwig scale), breast volume reduction, weight loss (15 kg), depression, but without menstrual disorders, normal blood pressure, and usage of oral contraceptives for more than 1 year without any improvement. We did blood tests for hormonal protocol for hyperandrogenemia and we found these values high 17 (OH) progesterone and all other androgen hormones. After these examinations, the patient was diagnosed with a non-classic form of CAH. CONCLUSION: Treatment with corticosteroids and other necessary treatment improved clinical and hormonal features.